Black heretics, black prophets radical political intellectuals - Bogues, Anthony (New York Routledge, 2003)
This pioneering new book surveys the political thought of a selection of influential black thinkers in provocative exploration of the black radical tradition as it has evolved in the Caribbean, Africa and the United States. Each chapter focuses on key figures or social movement including the slave Cugoano, the American anti-lynching activist Ida B. Wells-Barnett, C.L.R. James, W.E.B DuDois, former leader of the anti-colonial movement in Tanzania Julius Nyerere, Walter Rodney, the political philosophy of Rastafari and the activist-musican Bob Marley. This book is essential reading for anyone interested in the history of radical black thought and the development of an activist political tradition.
Includes bibliographical references and index.
Keywords: African Americans-Politics and government. African Americans-Intellectual life. African American intellectuals. African American radicals. Radicalism. Heresy. Blacks-Africa-Intellectual life. Blacks-Jamaica-Intellectual life. Blacks-Africa-Politics and government. Blacks-Jamaica-Politics and government